Soft Tıssue Changes In Skeletal Class Iıı Malocclusıon After Orthopedıc And Orthodontıc Treatment - Jalan Devecioğlu Kama; Sedat Baran; Osman Darı (Galenos Yayinevi, 1998)
In our study skeletal CI III cases have maxillary narrowness and the negative overjet, existence of soft tissue changes as a result of maxillary expansion and protraction have been investigated. The material of our study is existed from 30 cases have skeletal CI III anomaly applied Orthodontics Department of Faculty of Dentistry University of Dicle for treatment that 15 member of them had maxillary expansion and protraction treatment and the other untreated 15 had been control group. Biometric importance of differences in each group for provided values from measurements done on lateral cephalometric radiograms were compared with Wilcoxon test and importance of differences between groups with Mann-Whitney U test. In treatment group decreasing of face angle in p < 0.01 degree, decreasing of total soft tissue convexity and Ls-E dimension in p < 0.01 degree, increasing of upper lip length in p < 0.05 degree were found meaningful. In Control group increasing of nose height in p < 0.01 degree was meaningful. As a result with early maxillary expansion and protraction treatment in facial profile important changes are provided.